2012
DOI: 10.2196/jmir.2015
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adherence to Antiretroviral Therapy for Youth Living with HIV/AIDS: A Pilot Study Using Personalized, Interactive, Daily Text Message Reminders

Abstract: BackgroundFor youth living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS), nonadherence to antiretroviral therapy (ART) can lead to poor health outcomes and significantly decreased life expectancy.ObjectiveTo evaluate the feasability, acceptability, and preliminary efficacy of short message service (SMS) or text message reminders to improve adherence to ART for youth living with HIV/AIDS.MethodsWe conducted this prospective pilot study using a pre–post design from 2009 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
232
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(236 citation statements)
references
References 30 publications
3
232
0
1
Order By: Relevance
“…This method appears to overestimate adherence when compared with MEMS or laboratory-based measures of symptom status and functioning [93,94]. One study found text message reminders to be feasible and acceptable, however, response rates to requests about adherence were low (48 %) [95]. More research is needed on the use of these modalities for adherence measurement and intervention.…”
Section: Recommendations For Optimizing the Validity Of Self-report Mmentioning
confidence: 99%
“…This method appears to overestimate adherence when compared with MEMS or laboratory-based measures of symptom status and functioning [93,94]. One study found text message reminders to be feasible and acceptable, however, response rates to requests about adherence were low (48 %) [95]. More research is needed on the use of these modalities for adherence measurement and intervention.…”
Section: Recommendations For Optimizing the Validity Of Self-report Mmentioning
confidence: 99%
“…20 Text messaging has also been shown to improve treatment adherence and health outcomes in HIV patients. 21,22,23 Other examples include Text4Health-Adolescents, a randomized text messaging intervention, which facilitated improved immunization rates in a low-income, urban population. 24 Similarly, the Text4Baby campaign helped expectant mothers to receive prenatal information and other important resources.…”
Section: Introductionmentioning
confidence: 99%
“…The pilot study demonstrated that a daily, interactive, personalized text message reminder intervention is both feasible and acceptable and shows promise as a tool to help HIV-Positive youth adhere to ART. Larger controlled study would be needed to determine the impact of this intervention especially with focus on the process of developing the content with the participants [28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%